Percutaneous endoscopic gastrostomy (PEG) using a novel large-caliber introducer technique kit: a retrospective analysis - Toh Yoon, Ezekiel Wong; Yoneda, Kaori; Nakamura, Shinya; Nishihara, Kazuki (Endoscopy International Open, 2016)
Background and study aims: Percutaneous endoscopic gastrostomy (PEG) using the introducer technique is not only useful in patients with upper digestive tract stenosis but has been shown to reduce peristomal infection. In this study, we evaluated the safety and utility of a novel large-caliber introducer PEG kit (using 20 Fr size tube) compared with a push kit of similar size.Patients and methods: One hundred and thirty-six patients who received PEG at our hospital between January 2014 and December 2015 were retrospectively analyzed. Baseline characteristics, laboratory biomarkers, hemodynamic changes, postoperative adverse events and clinical outcomes with both kits were compared.Results: The new introducer PEG kit was used in 61 patients while the remaining 75 patients received tube placement using a push technique PEG kit. Except for the prevalence of dementia, which was lower in the introducer PEG kit group, baseline characteristics were similar in both groups. Tube placements were 100 % successful with both PEG kits and there were no significant differences in the change of postoperative hemodynamic or laboratory biomarkers. The Introducer PEG kit group experienced fewer incidence of feeding-related aspiration pneumonia (8.2 % vs. 24 %, P = 0.02), lower peristomal infection scores (1.2 vs. 1.6, P < 0.01), shorter postoperative length of stay (16 days vs. 23.7 days, P = 0.01) and fewer deaths at day 60 (3.3 % vs. 16 %, P = 0.02).Conclusions: Gastrostomy using the new large-caliber introducer PEG kit is safe and produced non-inferior (with some favourable) results when compared to the push technique using similar size tubes.